Hubungan Pola Makan dan Status Gizi dengan Tingkat Kebugaran Jasmani (Studi Komparasi Pada Siswa MAN Insan Cendekia Halmahera Barat dan SMA Negeri 11 Tidore Kepulauan) - Triana Nuryastuti; Safri Tinamba; Hary Chandra (Peneliti.net, 2021)
This research is motivated by differences in the eating habits of students of MAN Insan Cendekia West Halmahera (Boarding School) and students of SMA Negeri 11 Tidore Kepulauan (regular school). The purpose of this study was to determine whether there is a difference in the relationship between diet and nutritional status with the level of physical fitness of students in the two school models. This research was conducted at MAN Insan Cendekia and SMA Negeri 11 Tidore Kepulauan. The subjects of this study were 60 students of class X, consisting of 30 students from MAN Insan Cendekia and 30 students from SMA Negeri 11 Tidore Kepulauan. The data was collected by using a questionnaire and measurement test techniques. Dietary data were obtained using a 24-hour food recall instrument and a questionnaire, nutritional status data were obtained by measuring height, weight, arm circumference and head circumference calculating Body Mass Index (BMI), data on physical fitness levels using a 40 meter running test, jumping test. upright and sit down test to calculate the standard TKJI. The data analysis technique used product moment correlation with a significant level of 5%. The results of this study indicate that there is a relationship between diet and nutritional status with the level of physical fitness, namely the r table value of o, 361 <r count of 0.472 for regular schools and the value of r table of o, 361 <r count 0.538 for boarding school . These results indicate that there is no significant difference between regular school students (SMA Negeri 11 Tidore Kepulauan) and boarding school (MAN Insan Cendekia Halmahera Barat).